Excello: exploring spreadsheets for music composition - Mattinson, Henry; Sarkar, Advait (advait.org, 2020)
Excello is a spreadsheet-based music composition and programming environment. We co-developed Excello with feedback from 21 musicians at varying levels of musical and computing experience. We asked: can the spreadsheet interface be used for programmatic music creation? Our design process encountered questions such as how time should be represented, whether amplitude and octave should be encoded as properties of individual notes or entire phrases, and how best to leverage standard spreadsheet features, such as formulae and copy-paste. We present the user-centric rationale for our current design, and report a user study suggesting that Excello’s notation retains similar cognitive dimensions to conventional music composition tools, while allowing the user to write substantially complex programmatic music.